AT1 receptor signaling pathways in the cardiovascular system. (November 2017) - Kawai, Tatsuo; Forrester, Steven J.; O'Brien, Shannon; Baggett, Ariele; Rizzo, Victor; Eguchi, Satoru
Abstract: The importance of the renin angiotensin aldosterone system in cardiovascular physiology and pathophysiology has been well described whereas the detailed molecular mechanisms remain elusive. The angiotensin II type 1 receptor (AT1 receptor) is one of the key players in the renin angiotensin aldosterone system. The AT1 receptor promotes various intracellular signaling pathways resulting in hypertension, endothelial dysfunction, vascular remodeling and end organ damage. Accumulating evidence shows the complex picture of AT1 receptor-mediated signaling; AT1 receptor-mediated heterotrimeric G protein-dependent signaling, transactivation of growth factor receptors, NADPH oxidase and ROS signaling, G protein-independent signaling, including the β-arrestin signals and interaction with several AT1 receptor interacting proteins. In addition, there is functional cross-talk between the AT1 receptor signaling pathway and other signaling pathways. In this review, we will summarize an up to date overview of essential AT1 receptor signaling events and their functional significances in the cardiovascular system.